A Comparison between the Same-Ethnicity and Cross-Ethnicity Friendship Quality of Early Adults in Karachi - Ismail, Zeenat; Niaz, Madiha Umer; Rehman, Hiba (Advances in Social Sciences Research Journal, 2017)
This research compares the friendship quality of young adults between same ethnicity and cross ethnicity in Karachi. The participants were 200 in total and were divided into 100 majority ethnic group and 100 minor ethnicity group. They answered the McGill Friendship Questionnaire-Responder’s (MFQ-RA). The results showed that there was no significant difference in the same ethnicity friendship quality between ethnic majority and minority groups. However, the comparison of the same ethnicity and cross ethnicity friendship quality by gender shows a significant difference in both positive feelings and satisfaction. Females got significantly higher friendship satisfaction in cross ethnicity but no significant difference in positive feeling.